It Is Not an Anthropocene; It Is Really the Technocene: Names Matter in Decision Making Under Planetary Crisis - López-Corona, Oliver; Magallanes-Guijón, Gustavo (Frontiers in Ecology and Evolution, 2020)
We do not understand what we see but see what we understand. Words shape the comprehension of our environment and set the space of possibilities we can access when decision making. In here we make the case for the use of Technocene instead of Anthropocene using well-grounded arguments in basic scientific principles. We already know that the Earth system has co-evolved with life phenomena (i.e. the evolution of atmosphere chemistry). What the Technocene idea makes clear is that as modern human societies exhibit an enormous coupling with technology and for the first time in human history that technology has the potential to modify the very core processes that drive Earth System dynamics, then Technology must be considered as a new dimension of analysis in the study of Earth system in its coevolution with life and particularly human beings.